(untitled) (Research, Society and Development, 2020)
The Bolsa Família program articulates the transfer of income for the implementation of complementary programs, with the aim of promoting human development and the autonomy of the beneficiaries. In the municipality of Patos-PB, the Bolsa Família Program (PBF) has about 10,366 beneficiaries enrolled, there is a much greater demand for enrollees in the CadÚnico who are still waiting for their inclusion in the program. The main objective of this work is to evaluate the monitoring of the complementary actions of the Bolsa Família Program in the Municipality of Patos-PB. Documental and bibliographical researches were done, as well as semi-structured interviews with governmental actors and beneficiaries. The qualitative research was more adequate for the construction of this work. As for the methods of data collection, the case study follows. Being one of the greatest challenges of public policies, monitoring is seen as the continuous examination of processes, products, results and impacts of actions taken in implementation. The work did not achieve its main objective satisfactorily. As these actions have not yet begun to be offered to the beneficiaries directly, but indirectly in the CRAS, through improvement workshops, there is no consistent monitoring. Considering that the expectation of social inclusion is linked to access to public policies, the provision and follow-up of these actions by governmental spheres, are essential for the fight against poverty and hunger, contributing to the so-called exit doors of the Bolsa Família Program.